ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN PEMBERDAYAAN TERHADAP KOMITMEN ORGANISASI SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN - Idayanti Nursyamsi (Jurnal Keuangan dan Perbankan, 2013)
The success of banking institutions in providing excellent service to the customer was inseparable from theperformance of employees. This research aimed to study the influence of organizational citizenship behaviorand empowerment to organizational commitment and the influence to employee performance. Primary datawas taken by using questionnaires given to 128 employees by using Slovin formula. Path analysis model wasused to test the research hypothesis. The results showed that the level of employee performance positivelyinfluenced by organizational citizenship behavior, and employee empowerment and also comitment organizationalhad significant influence to employee performance. Improving the performance of employees was achallenge for banking institutions because employees were the important assets for the company.